Evaluasi Penilaian Pembelajaran PAI pada Kurikulum 2013 (K 13) dalam Tataran Praktek - Alwi Mudhofar (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
K13 curriculum which has been running since 2014 is able to change the mindsead of teachers to bring students to humans who are expected to have the character and competence. Learning evaluation is a series of activities to obtain, analyze, and interpret data about the learning process and learning outcomes of students carried out systematically and continuously. the problems that can be formulated include: 1). What is the input in the assessment of Islamic Religious Education learning in the 2013 Curriculum (K 13) ?, 2). What is the process of implementing the assessment of Islamic Religious Education learning in the 2013 Curriculum (K 13). Through field observations from several schools, it can be concluded; First, input evaluation, especially the qualifications of teaching staff in carrying out assessments including assessment design, indicators of competency achievement, assessment techniques and instruments, and how assessment processing has been met very well in accordance with established assessment standards. Second, the evaluation process (process), the assessment of the assessment system (affective, cognitive and psychomotor) and the implementation of the assessment process, shows the results that the process of carrying out the assessment of attitudes, knowledge and skills has been going well and conducive, only in the process of evaluating aspects of the teacher's attitude not going well.